Analiza porównawcza wybranych narzędzi Business Intelligence wspomagających systemy CRM - Radomiak, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article disscusses the basic principles of Customer Relationship Management and presents chosen tools of Business Intelligence (BI) class. The author presents definition and general profile of B1 tools, and formulates requirements in context of CRM systems supporting. Three products of the BI class that are available on the Polish computer market (MicroStrategy Desktop, STATISTICA Data Miner and System Górnik) are compared according to following criterions: the equipment requirements, database platform, available ways of data analysis, range of analytic functions particularly essential for CRM, the ways of information's presentation and co-operation with others applications. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 373-385